Septal and Hippocampal Neurons Contribute to Auditory Relay and Fear Conditioning - Xiao, Cuiyu; Liu, Yun; Xu, Jian; Gan, Xiong; Xiao, Zhongju (Frontiers in Cellular Neuroscience, 2018)
The hippocampus has been thought to process auditory information. However, the properties, pathway, and role of hippocampal auditory responses are unclear. With loose-patch recordings, we found that hippocampal neurons are mainly responsive to noise and are not tonotopically organized. Their latencies are shorter than those of primary auditory cortical (A1) neurons but longer than those of medial septal (MS) neurons, suggesting that hippocampal auditory information comes from MS neurons rather than from A1 neurons. Silencing the MS blocks both hippocampal auditory responses and memory of auditory fear conditioning trained with noise and tone. Auditory fear conditioning was associated with some cues but not with a specific frequency of sound, as demonstrated by animals trained with noise, 2.5-, 5-, 10-, 15-, or 30-kHz tones, and tested with these sounds. Therefore, the noise responses of hippocampal neurons have identified a population of neurons that can be associated with auditory fear conditioning.